One-step biosynthesis of hybrid reduced graphene oxide/iron-based nanoparticles by eucalyptus extract and its removal of dye. (1st December 2018) - Weng, Xiulan; Lin, Ze; Xiao, Xiaofeng; Li, Chengyang; Chen, Zuliang
Abstract: Green synthesis of nanomaterial using plant extract has recently attracted much scientific attention due to its simple operation and low cost. In this study, hybrid reduced graphene oxide/iron-based nanoparticles (RGO/Fe NPs) were synthesized via green route employing a one-step process with Eucalyptus leaf extract (EL). Hybrid RGO/Fe NPs were characterized by UV–vis spectrophotometer, Fourier transform infrared spectroscopy (FTIR), Transmission electron microscopy (TEM), Energy-dispersive spectrometer (EDS), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy (Raman). The results indicated that Fe NPs were spherical in shape, their diameter was 4–7 nm and they were uniformly dispersed on the surface of RGO. To understand the bioreduction conditions impacting on the yield of RGO/Fe NPs, testing the influence of various atmospheric conditions and the ratio of GO and ferric iron demonstrated that the content of RGO rose as the volume ratio of GO and ferric iron increased under nitrogen atmosphere. Adsorption of methylene blue (MB) using Fe NPs, RGO and hybrid RGO/Fe NPs revealed that the hybrid RGO/Fe NPs enabled superior adsorption of MB (199.4 mg/g). This suggests that RGO/Fe NPs has much potential in removing MB. Highlights: Hybrid RGO/Fe NPs were successfully synthesized by one step method. GO was converted into RGO by green method. Fe NPs were uniformly dispersed on the surface of RGO. Hybrid RGO/Fe NPs gave a high adsorption of MB (199.4 mg/g).